Trade Liberalisation and Effects on Pollutive Emissions and Waste A General Equilibrium Assessment for Norway - Taran Fæhn; Erling Holmøy (Statistics Norway, Research Department, 2001)
This paper assesses effects of the last decade's multinational liberalisation of foreign trade, in terms of economic gains and in terms of pollution. By means of a disaggregated intertemporal CGE model for Norway two scenarios with and without the trade reforms are compared. Despite a slight decrease in GDP, emissions of several pollutants rise significantly. This is partly attributable to a modest increase in aggregate welfare, as polluting consumption rise significantly along with reduced labour effort. Further, the trade reforms, in combination with existing policy concessions, result in a long-run structural change in favour of heavy-polluting export industries. As these are large consumers of electricity, prices of clean hydropower rise and cause an economy-wide substitution towards more pollutive energy sources.
Keywords: D58; D60; F13; Q25; 330; Trade Reforms; Welfare; Environment; Intertemporal CGE Model